A Clot Twist: Extreme Variation in Coagulotoxicity Mechanisms in Mexican Neotropical Rattlesnake Venoms - Seneci, Lorenzo; Zdenek, Christina N.; Chowdhury, Abhinandan; Rodrigues, Caroline F. B.; Neri-Castro, Edgar; Bénard-Valle, Melisa; Alagón, Alejandro; Fry, Bryan G. (Frontiers in Immunology, 2021)
Rattlesnakes are a diverse clade of pit vipers (snake family Viperidae, subfamily Crotalinae) that consists of numerous medically significant species. We used validated in vitro assays measuring venom-induced clotting time and strength of any clots formed in human plasma and fibrinogen to assess the coagulotoxic activity of the four medically relevant Mexican rattlesnake species Crotalus culminatus, C. mictlantecuhtli, C. molossus, and C. tzabcan. We report the first evidence of true procoagulant activity by Neotropical rattlesnake venom in Crotalus culminatus. This species presented a strong ontogenetic coagulotoxicity dichotomy: neonates were strongly procoagulant via Factor X activation, whereas adults were pseudo-procoagulant in that they converted fibrinogen into weak, unstable fibrin clots that rapidly broke down, thereby likely contributing to net anticoagulation through fibrinogen depletion. The other species did not activate clotting factors or display an ontogenetic dichotomy, but depleted fibrinogen levels by cleaving fibrinogen either in a destructive (non-clotting) manner or via a pseudo-procoagulant mechanism. We also assessed the neutralization of these venoms by available antivenom and enzyme-inhibitors to provide knowledge for the design of evidence-based treatment strategies for envenomated patients. One of the most frequently used Mexican antivenoms (Bioclon Antivipmyn®) failed to neutralize the potent procoagulant toxic action of neonate C. culminatus venom, highlighting limitations in snakebite treatment for this species. However, the metalloprotease inhibitor Prinomastat substantially thwarted the procoagulant venom activity, while 2,3-dimercapto-1-propanesulfonic acid (DMPS) was much less effective. These results confirm that venom-induced Factor X activation (a procoagulant action) is driven by metalloproteases, while also suggesting Prinomastat as a more promising potential adjunct treatment than DMPS for this species (with the caveat that in vivo studies are necessary to confirm this potential clinical use). Conversely, the serine protease inhibitor 4-(2-aminoethyl)benzenesulfonyl fluoride hydrochloride (AEBSF) inhibited the direct fibrinogen cleaving actions of C. mictlantecuhtli venom, thereby revealing that the pseudo-procoagulant action is driven by kallikrein-type serine proteases. Thus, this differential ontogenetic variation in coagulotoxicity patterns poses intriguing questions. Our results underscore the need for further research into Mexican rattlesnake venom activity, and also highlights potential limitations of current antivenom treatments.